Characterization of patients admitted with pneumonia and a negative diagnostic test for COVID-19 in the intensive care unit - Rodolfo Javier Rivero Morey; Lietter Aguilar Jure; Yenisel Chang Cuesta; Inte Santana Carballosa; Victor René Navarro Machado; Lya del Rosario Magariño Abreus (Medisur)
Background: in the wide context of the COVID-19 epidemic, secondary bacterial infections represent an important risk factor for the entity's adverse outcomes. Objective: to characterize patients admitted to the intensive care unit with a diagnosis of community-acquired pneumonia and negative for COVID-19. Methods: descriptive study, carried out between March/2020 and March/2021, in a series of 338 patients admitted to the Intensive Care Unit with a history of negative polymerase chain reaction to COVID-19, but with a diagnosis of acquired pneumonia in the community. Variables such as: age, sex, month of admission, requirement of artificial mechanical ventilation and condition at discharge were analyzed. Results: 60.3% of the patients were male, and the age group from 60 to 79 years old (50.3%) was the most representative. 31.7% required artificial mechanical ventilation, and 61.8% remained hospitalized for less than 48 hours. 61.6% were discharged alive, with an average stay of 6.31 ± 10.62 days. There were 218 hospitalized for more than 10 days from the onset of symptoms and the completion of the COVID-19 diagnostic test. Conclusions: during the epidemiological situation caused by COVID-19, patients were admitted to intensive care units with a diagnosis of community-acquired pneumonia not related to the SARS-Cov-2 virus. Timely treatment, in some cases artificial mechanical ventilation, even prolonged, contributed to the low lethality and discharge with a better quality of life.